To franchise or not to franchise: An analysis of decision rights and organizational form shares - Michael, Steven C. (Journal of Business Venturing, 1996)
For innovators and entrepreneurs in service businesses, franchising is frequently suggested as a way to succeed and grow. Academic research has provided little guidance for potential franchisors, however. This article provides a model to guide that choice of organizational form using results from agency theory. Analytically, franchising is a way to allocate decisions within the franchise system between the franchisor and the franchisee in order to promote efficiency and provide incentives. Franchisees make decisions regarding local operations, such as hours, prices, and locations, because they have the knowledge about local trading conditions. Franchisors make decisions regarding the product, its production, and associated marketing efforts that together create the standardization that the trademark signals. The revenue of franchise systems is divided to provide incentives to each party to support the allocation of decisions. Franchisors receive a percentage of gross sales, typically 5%, to compensate them for use of the trademark and associated services. Franchisees keep the unit's profits after paying royalties. These profits motivate the franchisee to make the good decisions that operate the unit efficiently. But franchising has limitations as well. First, by making franchisees invest in a unit in a specific geographic area, the franchise system exposes the franchisees to business risk; it consists of local economic conditions beyond franchisees' control that could reduce or eliminate their capital. That risk could be eliminated by owning a geographically diversified portfolio of shares of units in different places, but then incentives are weakened. Second, the requirements of standardization under the common trademark constrain franchisees from the full use of their human capital, including their knowledge of local conditions. Some adaptations to the local market are prohibited by the requirement of standardization. So high levels of either business risk or human capital in an industry make franchising a less desirable choice of organizational form. These ideas are tested with interindustry data using an econometric discrete choice model on the share of sales through franchise systems (termed organizational form share). The methodology is identical to market share models used in economics and marketing. Business risk, as measured by percent of units that have failed in the industry in the last 3 years, and human capital required in the industry, as measured by average wages paid, both negatively influence the share of sales through franchise systems. The model can be applied by entrepreneurs considering franchising, especially in industries not traditionally associated with franchising. Using public data sources identified in the study, a prospective franchisor can research the industry to determine if industry conditions support franchising as the optimal choice of organizational form. The empirical texts also suggest a second managerially relevant conclusion: the decision of “should we franchise?” can be and should be separated from the decision of “how do we implement franchising?” Factors previously shown to influence the implementation of franchising, the degree of ownership of units within the system, do not influence organizational form share, thus suggesting that the strategic decision of whether to franchise is distinct from the operating decision of how to implement franchising.